Kestabilan Emulsi dan Karakteristik Sensoris Low Fat Mayonnaise dengan Menggunakan Kefir sebagai Emulsifier Replacer - Herly Evanuarini; Nurliyani Nurliyani; Indratiningsih Indratiningsih; Pudji Hastuti (Faculty of Animal Science Universitas Brawijaya, 2016)
Mayonnaise is a kind of semi solid oil in water (o/w) emulsion which containing pasteurized egg yolk as an emulsifier. The consumers have demanded that the use of egg yolk be reduced. Kefir was used to develop a low fat mayonnaise as emulsifier replacer to egg yolk. The objective of this research was to observe the emulsion stability, sensory characteristics of low fat mayonnaise prepare during kefir as emulsifier replacer. The research method was using experimental design. The result showed that formulation of low fat mayonnaise by using Rice bran oil 40%, kefir 20% produces the optimal low fat mayonnaise in emulsion stability and accepted by the panelist.